Improvement in the Current Therapies for Hepatocellular Carcinoma Using a Systems Medicine Approach. Issue 6 (8th April 2020) - Ozcan, Mehmet; Altay, Ozlem; Lam, Simon; Turkez, Hasan; Aksoy, Yasemin; Nielsen, Jens; Uhlen, Mathias; Boren, Jan; Mardinoglu, Adil
Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer‐related death primarily due to the lack of effective targeted therapies. Despite the distinct morphological and phenotypic patterns of HCC, treatment strategies are restricted to relatively homogeneous therapies, including multitargeted tyrosine kinase inhibitors and immune checkpoint inhibitors. Therefore, more effective therapy options are needed to target dysregulated metabolic and molecular pathways in HCC. Integrative genomic profiling of HCC patients provides insight into the most frequently mutated genes and molecular targets, including telomerase reverse transcriptase, the TP53 gene, and the Wnt/β‐catenin signaling pathway oncogene (CTNNB1). Moreover, emerging techniques, such as genome‐scale metabolic models may elucidate the underlying cancer‐specific metabolism, which allows for the discovery of potential drug targets and identification of biomarkers. De novo lipogenesis has been revealed as consistently upregulated since it is required for cell proliferation in all HCC patients. The metabolic network‐driven stratification of HCC patients in terms of redox responses, utilization of metabolites, and subtype‐specific pathways may have clinical implications to drive the development of personalized medicine. In this review, the current and emerging therapeutic targets in light of molecular approaches and metabolic network‐based strategies are summarized, prompting effective treatment of HCC patients. Abstract : The development of high‐throughput sequencing techniques and network driven analysis has revolutionized the knowledge and opened up a new route to investigate underlying genomic alterations and cancer‐specific metabolism. This review provides an overview of the current and emerging therapeutic targets and therapies in light of molecular and metabolic network‐based approaches, prompting the more effective treatment of hepatocellular carcinoma patients.